Conflicts at Sea. Diving with Sharks in New Zealand (Revista LIDER, 2019)
This exploratory research examines an interesting conflict, between stakeholders, over the use of goods or resources commonly used for tourism. Methodologically, the analysis is based on a case study with a qualitative approach, which records semi-structured interviews, participant observation and analysis of relevant documents related to the case. Since, in 2008, operators outside the community began offering shark cage diving experiences in Stewart Island, New Zealand, the local community has been strongly opposed to this activity, especially by commercial divers working in these waters extracting abalones. They think that shark feeding by tour operators could affect the behavior of these predators, endangering not only their livelihoods, but also their lives. The present research seeks to describe, characterize and analyze the given conflict, identifying the key aspects that could be hindering its solution. For this, the conflict is studied using the management approach called Adaptive Comanagement. This approach was used as an analysis paradigm because it has proven to be an efficient tool for resolving conflicts based on the use of common use resources, especially because it allows the parties involved to learn from each other, allowing them to deal with management problems that are, at each time, more complex through the generation of procedures that allow to solve present and future conflicts in an efficient way. The conflict analysis shows the absence of efforts by both parties to try to reach a solution due to strong antagonistic positions, and the lack of trust being a key obstacle to collaboration. In addition, there is evidence of the lack of leadership that guides the parties towards an understanding. This case offers an interesting opportunity to observe the complexity of socio-ecological systems as a common resource source.